Conservação de Lachesis muta (Linnaeus, 1766) (serpentes: Viperidae) no estado do Ceará, Brasil: aspectos geográficos, biológicos e ecológicos - Santos, Thabata Cavalcante dos (2023)
Lachesis muta is a species of venomous snake that occurs in the humid forests of South America. In Brazil it has two subspecies with populations with different distributions, Lachesis muta muta which inhabits the Amazon rainforest and Lachesis muta rhombeata distributed in the Brazilian Atlantic Forest. In the state of Ceará, the species only has a confirmed distribution in the highlands of the Baturité Massif, a remnant of humid forest surrounded by the semi-arid region. To date, information about its life history, distribution and conservation in Ceará is unknown. To increase understanding of the local distribution of Lachesis muta in Ceará, Chapter I carried out a survey of historical and recent records of the species, calculating its extent of occurrence (EOO), area of occupation (AOO) and altitudinal gradient. Ninety-two georeferenced records were compiled, ten historical and 82 recent, for the cities of Guaramiranga, Pacoti, Baturité and Mulungu in the Baturité Massif. The species has a restricted distribution in humid forest areas, with an EOO of 98.47 km2, an AOO of 91.40 km2 and an altitudinal gradient of 900 to 350 m at sea level. Chapter II investigates the biological, environmental and population aspects of Lachesis muta in the state of Ceará. We sampled 26 individuals, 13 live (6 males and 7 females) and 13 dead (8 males and 5 females). In terms of biological aspects, it was possible to observe that the males have a larger body size than the females, which was reflected in the sexual dimorphism in the tail. We also observed that L. muta has a preference for primary vegetation environments, although it was also found in secondary vegetation areas with human intervention. We analyzed the behavior of 13 individuals at four different times, observing that 38.46% were curled up during the encounter, while during capture and sorting, fleeing behavior was the most observed, 45.45% and 39.10%, respectively. On release, 50% of the individuals exhibited slow and gradual locomotion behavior. We can see that L. muta also has a low population density in its EOO in the Baturité Massif, as no individuals were observed during the active day and night searches. For Chapter III, we analyzed the contribution of citizen science (CS) during this study, raised the threats associated with the species and analyzed its threat status based on the IUCN criteria. Society contributed significantly to this study, allowing us to obtain a total of 26 sampled individuals and 82 recent records of L. muta through the alert system, as well as obtaining a new record of Bothrops bilineatus for the state of Ceará. We observed that the EOO of L. muta is losing forest area and gaining non-vegetated areas and savannas. Habitat loss, associated with geographic and genetic isolation, killing and indiscriminate trampling are the main threats to L. muta in its EOO. Due to these factors, we suggest categorizing it as Critically Endangered in the territory of Ceará.